Impact of dental treatments under general anesthesia on oral health-related quality of life in children: a comprehensive meta-analysis - Nasibe Aycan Yilmaz; Mehmet Emin Arayici; Candan Efeoglu (BMC Oral Health)
Abstract Background Children’s oral health significantly impacts their overall well-being, daily activities, and social interactions. Dental treatments under general anesthesia are often required for extensive dental problems, special health care needs, or dental phobias, particularly in pediatric populations. The objective of this meta-analysis was to systematically review and synthesize existing research on how dental treatments under general anesthesia affect the oral health-related quality of life (OHRQoL) in children. Methods The electronic databases such as PubMed, EMBASE, Ovid MEDLINE, Web of Science, and Scopus were systematically reviewed following PRISMA guidelines to identify studies evaluating OHRQoL changes after dental treatments under general anesthesia. Studies involving ECOHIS and COHRQoL scales in pre- and postoperative assessments were included. The mean differences between scale measurements before and after dental treatments under general anesthesia were reported as the standard mean difference (SMD), and effect sizes for Hedges’ g were classified as follows: small effect (0.2), medium effect (0.5), large effect (0.8). All meta-analysis statistical computation was carried out using the Hartung-Knapp-Sidik-Jonkman method for the random effects model. Results A total of 36 papers satisfied the inclusion criteria and were subsequently included in the investigation. In the pooled analysis, treatments under general anesthesia in children improved OHRQoL (ECOHIS) in the short term with a significantly large effect size (SMD = 1.66, 95% CI: 1.07–2.24, p < 0.001; τ2 = 2.18, I2 = 98.9, p < 0.001). Similarly, dental treatment under general anesthesia increased the COHRQoL score in children with a significantly large effect size (SMD = 1.32, 95% CI: 0.81–1.84, p < 0.001; τ2 = 0.78, I2 = 97.3, p < 0.001). Conclusion The findings of this meta-analysis suggest that there was evidence that OHRQoL of children receiving dental treatment under general anesthesia improves with a large effect size in the short-term following treatment.